Correlation of vertical parameters with facial proportions: cephalogram evaluation of class II malocclusion cases at the orthodontic clinic - Dina Ardananeswari; Krisnawati Krisnawati; Nia Ayu Ismaniati (Faculty of Dentistry, Universitas Gadjah Mada, 2026)
Class II malocclusion exhibits a significant correlation with diverse vertical skeletal patterns. Various vertical analyses have been widely used to see the height of face, but their reference points produce different interpretations. Therefore, it is necessary to use more than one vertical parameter as a reference in establishing orthodontic diagnosis and treatment plans. In addition, facial proportions can also be used to assess vertical components. Moving on from this, it will be known whether there is a correlation of vertical parameters with facial proportions in cases of class II malocclusion in non-growing individuals ages > 19 years. Discover the correlation between vertical parameters and facial proportions in skeletal class II malocclusion. A total of 65 cephalometric class II malocclusions that met the inclusion and exclusion criteria were obtained from the Orthodontic Clinic of Faculty of Dentistry, Universitas Indonesia. The cephalogram was measured to determine the angles of A point to B point (ANB), maxillary mandibular plane angle (MMPA), lower anterior facial height (LAFH) and facial axis. The correlation between MMPA and LAFH was analyzed using the Spearman correlation test, while the facial axis and LAFH were analyzed using the Pearson correlation test. Average class II malocclusion patients have a mean ANB value of 7.03º with an MMPA angle of 30.78º. The average portion of LAFH is 55.05% with a facial axis of 84.11º. The findings of this study indicate that there is a correlation between MMPA and LAFH, but there is no correlation between facial axis and LAFH. This study indicates that greater MMPA angle values of class II malocclusion in non-growing patients ages > 19 years will result in a high lower proportion, and vice versa.